2016
DOI: 10.2460/ajvr.77.6.641
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of bupivacaine after intraperitoneal administration to cats undergoing ovariohysterectomy

Abstract: OBJECTIVE To evaluate pharmacokinetics of bupivacaine after IP administration to cats undergoing ovariohysterectomy. ANIMALS 8 healthy cats. PROCEDURES Anesthesia was induced with propofol and maintained with isoflurane. Buprenorphine (0.02 mg/kg, IV) and meloxicam (0.2 mg/kg, SC) were administered. A 20-gauge catheter was inserted into a jugular vein for blood sample collection. A ventral midline incision was made, and a solution of 0.5% bupivacaine (2 mg/kg) diluted with an equal volume of saline (0.9% NaCl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
2
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 40 publications
(42 reference statements)
0
60
2
8
Order By: Relevance
“…A trend towards the decrease in hospitalization time was observed with the use of the IP technique which was not significantly, but could be clinically relevant to an individual cat while reducing stress and costs with hospitalization. IP administration of bupivacaine has shown to be safe and to provide postoperative analgesia in cats undergoing OVH [3, 4], and it has been made part of the standard analgesic protocol for SUB placement at the authors’ institution. In human medicine, many studies have reported the benefits of local anesthetics to reduce risk factors associated with morbidity or to accelerate recovery [9].…”
Section: Discussionmentioning
confidence: 99%
“…A trend towards the decrease in hospitalization time was observed with the use of the IP technique which was not significantly, but could be clinically relevant to an individual cat while reducing stress and costs with hospitalization. IP administration of bupivacaine has shown to be safe and to provide postoperative analgesia in cats undergoing OVH [3, 4], and it has been made part of the standard analgesic protocol for SUB placement at the authors’ institution. In human medicine, many studies have reported the benefits of local anesthetics to reduce risk factors associated with morbidity or to accelerate recovery [9].…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence that these techniques should replace other analgesics such as nonsteroidal anti‐inflammatory drugs (NSAIDs) but, rather, should be used in addition. IP and incisional analgesia should be used as part of a multimodal analgesic plan (Benito et al . ). For example, the combination of an opioid, NSAID and IP and incisional anaesthesia provides adequate postoperative analgesia in cats undergoing ovariohysterectomy (Benito et al .…”
Section: Indications For Ip and Incisional Anaesthesiamentioning
confidence: 97%
“…For example, the combination of an opioid, NSAID and IP and incisional anaesthesia provides adequate postoperative analgesia in cats undergoing ovariohysterectomy (Benito et al . ). Total doses of bupivacaine 0.5% should not exceed 4 mg/kg in dogs and 2 mg/kg in cats (Benito et al . , , ).…”
Section: Indications For Ip and Incisional Anaesthesiamentioning
confidence: 97%
See 2 more Smart Citations